2010
DOI: 10.1074/jbc.m110.165068
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Linear Heterogeneity of Amyloid β Protein Fibrils Revealed by Higher Resolution Mass-per-length Determinations

Abstract: Amyloid ␤ proteins spontaneously form fibrils in vitro that vary in their thermodynamic stability and in morphological characteristics such as length, width, shape, longitudinal twist, and the number of component filaments. It is vitally important to determine which variant best represents the type of fibril that accumulates in Alzheimer disease. In the present study, the nature of morphological variation was examined by darkfield and transmission electron microscopy in a preparation of seeded amyloid ␤ protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 55 publications
1
44
0
Order By: Relevance
“…25 The 2D-IR measurements reported herein now indicate that there are heterogeneities and mobile water molecules within Aβ fibril filaments, and that they lead to an evolution of secondary internal fibril structure over long times. These conclusions are significant to molecular modeling efforts aimed at understanding the formation of amyloid fibrils, and at the design of diagnostic or therapeutic agents that target amyloid fibrils.…”
Section: ■ Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…25 The 2D-IR measurements reported herein now indicate that there are heterogeneities and mobile water molecules within Aβ fibril filaments, and that they lead to an evolution of secondary internal fibril structure over long times. These conclusions are significant to molecular modeling efforts aimed at understanding the formation of amyloid fibrils, and at the design of diagnostic or therapeutic agents that target amyloid fibrils.…”
Section: ■ Discussionmentioning
confidence: 98%
“…27 It is also unlikely that these fibrils disaggregated and then reaggregated into a different structure over the span of 4 years because the equilibrium monomer concentrations for these samples were measured and found to be undetectable. 25 Chemical changes such as deamidation are possible, and may alter the pathways and kinetics of fibril formation. 37 However, the excitonic structure and morphological appearance of the 4-year-old fibrils in this study are unchanged, and the changes observed are often associated with fast spectral diffusion suggesting that they are due to the presence of mobile water molecules.…”
Section: Cmentioning
confidence: 99%
“…Whether the peptide aggregates before interacting with the membrane depends on the local A␤ concentration, which can be affected by a variety of factors, such as the efficiency of A␤ elution from the membrane and the clearance of existing A␤ aggregates. In addition, the critical concentration of aggregation for A␤ peptides may also vary in a broad range, from below 0.1 M to above 10 M, as determined previously using a number of techniques (45)(46)(47)(48). Therefore, the interactions between A␤ and the membrane may start from a highly heterogeneous system that involves the co-existence of A␤ monomers and small and large oligomers.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Previous studies involving in situ atomic force microscopy (AFM) or transmission electron microscopy (TEM) have revealed Aβ42 fibrillogenesis to proceed via the formation of highmolecular-weight protofibrils. 11,12 The kinetics of protofibril formation and stability and the structure of the final fibrils depend greatly upon ambient conditions such as pH, temperature, buffer composition, and peptide concentration, [13][14][15][16][17][18][19][20] as well as upon the hydrophobicity or hydrophilicity of the substrate. 21 Although the mechanism underlying the aggregation of Aβ peptides in vitro has been the subject of numerous investigations over the past two decades, many fundamental questions remain unanswered.…”
Section: Introductionmentioning
confidence: 99%